Implementasi Pendekatan Belajar Bervariatif dalam Meningkatkan Kedisiplinan Peserta Didik Fase E pada Mata Pelajaran Al-Qur’an Hadits - Raito Raito; Intan Sri Wahyuni (STAI Al-Musaddadiyah Garut, 2026)
Student discipline is very important, but the discipline of phase E students is still low, indicated by students who are still late to class, use mobile phones during the learning process, and are late in submitting assignments. The success of learning is highly dependent on the application of varied methods, by presenting diverse methods, learning not only becomes more inclusive, but also students can understand the material in depth, stimulate creativity, and build higher motivation and involvement, thus making students more disciplined in the learning process. The purpose of this study is to describe the implementation of a varied learning approach in improving the discipline of phase E students in the Al-Qur'an Hadith subject at MAN 1 Garut. This study uses a descriptive qualitative analysis method. Data collection methods are by observation, interviews, and documentation studies. The data sources used in this study are primary sources, namely data sources obtained directly from the results of observations and interviews conducted with information providers and secondary sources, namely books, journals, the internet and so on. The data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of a varied learning approach can improve the discipline of Phase E students in the Al-Qur'an Hadith subject at MAN 1 Garut. Keywords: Al-Qur’an Hadith, Student Discipline, Varied Learning Approaches